A comparative investigation of fixed and free-running CFD self-propulsion models on a waterjet-propelled trimaran. (15th July 2021) - Zhang, Lei; Wei, Yuanhui; Deng, Yusi; Yin, Han; Zhang, Yi; Shang, Yuchen; Zhang, Jianing
Abstract: The numerical method for self-propulsion (SP) point prediction is an essential part of ship hydrodynamics. However, comprehensive investigations on different CFD SP model characteristics are rare, especially for the high-performance waterjet-propelled trimarans. This paper proposes four types of overset mesh-based CFD SP numerical models on a waterjet-propelled trimaran model: two PID-controlled free-running SP models with/without a moving background and two surge-fixed SP models with/without the propulsor PID controller. The URANS CFD simulations are conducted by following the Verification and Validation (V&V) procedure to investigate the four SP models' characteristics. The four computed model SP points agree well with the experimental result, and both the finest grid relative errors are within 1.5%. A comprehensive comparison of the consumed computing resources, surge freedom, control strategy, simulation scheme, V&V result, simulated flow field, simulation accuracy, and calculation efficiency of the four SP models are analyzed. Both the PID-controlled free-running SP model with a moving background and the PID-controlled surge-fixed SP model show advantages in terms of computing resource consumption, propulsor control strategy, accuracy, and efficiency. In particular, compared with the conventional fixed SP model, the computational efficiency could be promoted up to 150%, and the time consumption could decrease up to 60%. Furthermore, the PID-controlled free-running CFD model with moving background shows its advantages and potential in directly simulating the ship's real-time motion in various complex environments. Highlights: Four self-propulsion (SP) CFD models are proposed for a waterjet-propelled trimaran: two free-running and two fixed. The computed four SP points agree well with the experimental model test result and show the same accuracy level. The PID-controlled free-running SP model with a moving background shows the comprehensive advantages. Computational efficiency promotes up to 150% using the above free-running model compared with the conventional fixed model.